Faktor determinan pemilihan auditor eksternal yang berkualitas - ITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The purpose of this research is to analyze the impact of corporate governance mechanism, company's complexity, demand of the external financing and leverage towards the selection of external auditors who can provide high quality audit in Indonesia. This research also uses company's size, foreign ownership and family ownership as control variables. Hypothesis testing is carried out by using logistic regression model using 203 observation with the sample taken from listed companies on the Indonesia Stock Exchange in 2007 except bank and other financial institutions. This study concludes that corporate governance mechanism increases the probability of selecting external auditirs who can provide high quality unit. Company's complexity has a significant influence towards the selection of external auditors although it has a negative correlation leverage do not have any influence on the selection of the external auitors with high quality audit.